The local pulsatile parathyroid hormone delivery system induces the osteogenic differentiation of dental pulp mesenchymal stem cells to reconstruct mandibular defects - Yuanyuan Jia; Mianmian Duan; Yan Yang; Duchenhui Li; Dongxiang Wang; Zhenglong Tang (Stem Cell Research & Therapy)
Abstract Background Tumors and injuries often lead to large mandibular defects. Accelerating the osteogenesis of large bone defect areas is a major concern in current research. In this study, dental pulp mesenchymal stem cells (DPSCs) were used as seed cells, and the local pulsatile parathyroid hormone (PTH) delivery system was used as an osteogenic-inducing active ingredient to act on DPSCs and osteoblasts, which were applied to the jaw defect area to evaluate its therapeutic effect on bone regeneration. Methods Pulsatile delivery systems, both with and without PTH, were developed following the protocols outlined in our previous study. In vitro, the biocompatibility of the pulsatile delivery system with DPSCs was assessed using the Cell Counting Kit-8 (CCK8) assay and live/dead cell staining. Osteogenic differentiation was evaluated through alkaline phosphatase staining and alizarin red staining. In vivo, critical bone defects with a diameter of 10 mm were created in the mandibles of white rabbits. The osteogenic effect was further assessed through gross observation, X-ray imaging, and histological examination. Results In vitro experiments using CCK8 assays and live/dead cell staining demonstrated that DPSCs successfully adhered to the surface of the PTH pulsatile delivery system, showing no significant difference compared to the control group. Furthermore, alkaline phosphatase staining and Alizarin Red staining confirmed that the localized pulsatile parathyroid hormone delivery system effectively induced the differentiation of DPSCs into osteoblasts, leading to the secretion of abundant calcium nodules. Animal studies further revealed that the PTH pulsatile delivery system promoted the osteogenic differentiation of DPSCs, facilitating the repair of critical mandibular bone defects. Conclusion The rhythmic release of PTH from the pulsatile delivery system effectively induces the osteogenic differentiation of DPSCs. By leveraging the synergistic interaction between PTH and DPSCs, this approach facilitates the repair of extensive mandibular bone defects.